2014
DOI: 10.1186/s12861-014-0042-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic target of rapamycin complex 1 signaling regulates cell proliferation, cell survival, and differentiation in regenerating zebrafish fins

Abstract: BackgroundThe mechanistic target of rapamycin complex1 (mTORC1) signaling pathway has been implicated in functions of multicellular processes, including cell growth and metabolism. Although recent reports showed that many signaling pathways, including Activin, Bmp, Fgf, sonic hedgehog, Insulin-like growth factor (IGF), Notch, retinoic acid, and Wnt, are implicated in non-mammalian vertebrate regeneration, also known as epimorphic regeneration, mTORC1 function remains unknown.ResultsTo investigate the role of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 40 publications
8
44
0
Order By: Relevance
“…While epicardium, endocardium and coronary vessels also regenerate [16][17][18]19 ], the majority of studies published so far have concentrated on the cellular and molecular mechanisms of cardiomyocyte regeneration. Genetic lineage tracing has shown that cardiomyocytes regenerate from spared differentiated cardiomyocytes, which dedifferentiate and re-enter the cell cycle (Figure 1a) 54], Activin [55], Calcineurin [56 ], Hippo (YAP) [57], and mTor [58], while heart regeneration requires PDGF [59], TGFb [34,60], Jak/Stat [61 ], Neuregulin [62] and NF-kB [63].…”
Section: Cellular Basis Of Fin and Heart Regenerationmentioning
confidence: 99%
“…While epicardium, endocardium and coronary vessels also regenerate [16][17][18]19 ], the majority of studies published so far have concentrated on the cellular and molecular mechanisms of cardiomyocyte regeneration. Genetic lineage tracing has shown that cardiomyocytes regenerate from spared differentiated cardiomyocytes, which dedifferentiate and re-enter the cell cycle (Figure 1a) 54], Activin [55], Calcineurin [56 ], Hippo (YAP) [57], and mTor [58], while heart regeneration requires PDGF [59], TGFb [34,60], Jak/Stat [61 ], Neuregulin [62] and NF-kB [63].…”
Section: Cellular Basis Of Fin and Heart Regenerationmentioning
confidence: 99%
“…We speculate that the corresponding changes in expression had an impact on the TORC1 targets, p70 S6 kinase (S6K) and eIF4E-binding protein-1 4E-BP1, which regulate translation of mRNA. Inhibition of TORC1 signaling from 24 to 72 h after amputation in a zebrafish fin regeneration model suppressed cell proliferation through the inhibition of S6K activation (Hirose et al 2014). Thus, we speculate that it suppressed cell proliferation through the inhibition of S6K activation in B. calyciflorus.…”
Section: Discussionmentioning
confidence: 96%
“…A surprising discovery was that the TOR expression levels reached a maximum 20-fold increase (p < 0.001) and S6K reached a 15-fold increase (p < 0.001). Rapamycin inhibition of p70S6K and cell cycle activity is closely associated with many different key cellular processes, but in a cell-free system, a rapamycin-PKBP complex did not inhibit p70S6K activity, which showed that there was no direct interaction between rapamycin and p70S6K (Hirose et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Following caudal fin amputation in zebrafish, TOR signaling, reflected by the levels of the phosphorylated form of S6K (S6 Kinase), is active in wound epidermal cells, osteoblasts and proliferative proximal region of the blastema [17] (Figure 2a). During regenerative outgrowth, mTORC1 inhibition (with rapamycin treatment) suppresses blastema formation.…”
Section: Mtor Signaling Involvement During Appendage Regenerationmentioning
confidence: 99%